2020
DOI: 10.1038/s41598-020-74455-5
|View full text |Cite
|
Sign up to set email alerts
|

Online proprioception feeds plasticity of arm representation following tool-use in healthy aging

Abstract: Following tool-use, the kinematics of free-hand movements are altered. This modified kinematic pattern has been taken as a behavioral hallmark of the modification induced by tool-use on the effector representation. Proprioceptive inputs appear central in updating the estimated effector state. Here we questioned whether online proprioceptive modality that is accessed in real time, or offline, memory-based, proprioception is responsible for this update. Since normal aging affects offline proprioception only, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…In healthy adults, the explicit representation of the body metrics (or Body Image) has been shown to be largely immune to the effects of tool use. When required to indicate their forearm length using the same paradigm as in the present study, adults' performance shows that the explicit knowledge of their forearm length is not modified after tool use (Bahmad et al, 2020;Cardinali et al, 2011Cardinali et al, , 2012Martel et al, 2019). Yet, this is not the case during development: TD children and adolescents judge their forearm as being shorter after tool use (Martel et al, 2021), a sign of their Body Image plasticity.…”
Section: Children and Early Adolescents With Dcd Have A Preserved Abi...mentioning
confidence: 59%
See 1 more Smart Citation
“…In healthy adults, the explicit representation of the body metrics (or Body Image) has been shown to be largely immune to the effects of tool use. When required to indicate their forearm length using the same paradigm as in the present study, adults' performance shows that the explicit knowledge of their forearm length is not modified after tool use (Bahmad et al, 2020;Cardinali et al, 2011Cardinali et al, , 2012Martel et al, 2019). Yet, this is not the case during development: TD children and adolescents judge their forearm as being shorter after tool use (Martel et al, 2021), a sign of their Body Image plasticity.…”
Section: Children and Early Adolescents With Dcd Have A Preserved Abi...mentioning
confidence: 59%
“…As recalled in the introduction, TD children and early adolescents show a tool-induced kinematic pattern opposite to adults (Baccarini et al, 2014;Bahmad et al, 2020;Cardinali et al, 2009Cardinali et al, , 2011Martel et al, 2019): after tool use, their kinematics display increased peak amplitudes and decreased peak latencies in several parameters of the reaching phase of their free-hand movements, resulting in shorter movement times (Martel et al, 2021). While it is presently uncertain whether it results from vision-biased motor control of tools, or the establishment of new sensorimotor associations (or both), this pattern is consistent with a change in the arm length estimate, in the direction of shortening.…”
Section: Body Estimate Plasticity Is Altered In Dcd Children and Earl...mentioning
confidence: 88%
“…In healthy adults, the explicit representation of the body metrics (or body image) has been shown to be largely immune to the effects of tool use. When required to indicate their forearm length using the same paradigm as in the present study, adults performance show that the explicit knowledge of their forearm length is not modified after tool use (Bahmad et al, 2020;Cardinali et al, 2011Cardinali et al, , 2012Martel et al, 2019). Yet, this is not the case during development: TD children and adolescents judge their forearm as being shorter after tool use (Martel et al, 2021).…”
Section: Children and Early Adolescents With Dcd Have A Preserved Ability To Update The Explicit Metrics Of Their Bodymentioning
confidence: 67%
“…As alluded to in the introduction, TD children and early adolescents show a tool-induced kinematic pattern opposite to adults (Baccarini et al, 2014;Bahmad et al, 2020;Cardinali et al, 2009Cardinali et al, , 2011Martel et al, 2019): after tool use, their kinematics display increased peak amplitudes and decreased peak latencies in several parameters of the reach phase of their free-hand movements, resulting in shorter movement times (Martel et al, 2021). While it is presently uncertain whether it results from vision biased motor control of tools, or the establishment of new sensorimotor associations (or both), this pattern is consistent with a change in the arm length estimate in the direction of its shortening.…”
Section: Body Estimate Plasticity Is Altered In Dcd Children and Early Adolescentsmentioning
confidence: 97%
“…In the early 20 th century, the British neurologists Henry Head and Gordon Holmes even noted that our bodily senses of location and movement extend with hand-held instruments (Head & Holmes, 1911). Though it took over eighty years for this claim to begin to be researched empirically (Maravita & Iriki, 2004; Martel, Cardinali, Roy, & Farne, 2016), numerous studies in the last three decades have found that tools influence numerous neurocognitive processes underlying perception (Canzoneri et al, 2013; Cardinali et al, 2011; Miller, Cawley-Bennett, Longo, & Saygin, 2017; Miller, Longo, & Saygin, 2014; Reed, Betz, Garza, & Roberts, 2010; Sposito, Bolognini, Vallar, & Maravita, 2012; Witt, Proffitt, & Epstein, 2005) and action (Bahmad et al, 2020; Berti & Frassinetti, 2000; Biggio, Bisio, Avanzino, Ruggeri, & Bove, 2020; Cardinali, Brozzoli, Finos, Roy, & Farnè, 2016; Cardinali et al, 2009; Farnè, Iriki, & Làdavas, 2005; Ganesh, Yoshioka, Osu, & Ikegami, 2014; Iriki, Tanaka, & Iwamura, 1996; Martel et al, 2019; Umiltà et al, 2008). However, most of this research has focused almost exclusively on the effects of controlling a tool (Johnson-Frey, 2004), ignoring the fact that tools also extend our ability to sense the environment (Vaught, Simpson, & Ryder, 1968).…”
Section: Introductionmentioning
confidence: 99%